The impact of remittances on financial sector development: An exploration in the SADC region - Denoon-Stevens, Catherine A (Research of GSB, 2018)
Remittances received from migrants abroad have become one of the largest sources of external finance for developing countries. It has been argued that a particular impact of this influential flow is the stimulation of financial sector development. However, current research has been mainly based at a broad level across the developing world. This paper investigates whether this consensus holds true when examined at a sub-regional level within Sub-Saharan Africa. It is an important question given the extensive literature documenting the direct growth enhancing effect of financial development, and consequently, poverty reduction. In particular, annual data from 11 countries in the South African Development Community (SADC) are analysed from 1990 to 2011 using the panel data analysis techniques of fixed and random effects models, a Generalised Methods of Moments (GMM) dynamic framework (Arellano & Bover, 1995) and Instrumental Variables (IV) Estimations (Baum, Schaffer & Stillman, 2003). Three indicators of financial sector development are analysed, namely: the level of bank deposits, near money (M2) and credit intermediated by the local banking sector. Remittances are found to have a largely negative and insignificant impact on financial sector development in SADC over the period of study. This contradicts the findings of the current literature on this topic. The implications of this are noteworthy as it adds evidence that the model currently held in the literature (i.e. that remittances have a positive and significant relationship on financial sector development) is not robust at the less smoothed level of a subregional scale. But further, it provides evidence to motivate the further exploration of the impact of measurement errors of remittance flows. Recommendations for further research are provided on the basis of both these possible causes.